Resveratrol em preparação de uso tópico como preventiva ao envelhecimento cutâneo: revisão sistemática - Marubayashi, Bruna Aparecida dos Santos (2020)
Resveratrol (RSV) is a polyphenol, a secondary metabolite of vegetables that aims to protect the plant against bacteria, fungi, UV radiation, among others. Several studies of its properties show health benefits, such as antiviral, anticancer, neuroprotective, anti-aging, and anti-inflammatory activity. In the cosmetic area, RSV is used topically in anti-aging products due to its antioxidant activity. The main environmental factor that causes skin aging is UV radiation, and its long-term effects are the formation of wrinkles, marks, and tissue damage. Objective: To evaluate, through systematic review, scientific evidence that proves the antioxidant activity of RSV in preparation for topical use as a preventive to photoaging. Methods: The research was carried out in the Cochrane, Scielo, Science Direct, Pubmed, Web of Science, and Scopus databases, considering the search terms "Resveratrol" OR "Trans-resveratrol" AND "Antioxidants" AND "Photoaging," in addition to manual searches of articles and journals, without language restriction. Data published from 1999 to March 2020 were considered, given the increased interest in this compound. The recovered articles were analyzed through titles and abstracts and evaluated according to the pre-established inclusion criteria, namely, publications with in vitro and in vivo tests without comorbidities in the skin and exclusive supplementation of RSV topically as an antioxidant. The data of interest were taken from the selected articles, analyzed, and compared, following the PRISMA Checklist's guidelines. The Cochrane tool was used to assess clinical trials' quality and the SYRCLE tool for experimental animal studies. Results: 714 articles were found; after screening and eligibility, 8 met all criteria and were included for data extraction. The quality assessment showed that the information contained in the study in animals is uncertain, as there is no description about randomization of the experiments and the concealment in the allocation of the case and control groups, and, in the study in humans, there are also uncertainties, since it was not performed according to the double-blind method and division of results between different age groups. The studies were organized in tables according to the research design. Cell studies have shown a decrease in the production of reactive oxygen by the application of RSV, activation of collagen-forming genes, and a decrease in pro-apoptotic proteins; in animals, there was a decrease in the level of fat peroxidation (oxygen reactive generation mechanism), and in humans, we observed an improvement in skin elasticity. Discussion: HaCaT cells are the most prominent choice, as they efficiently reproduce human skin. Oral RSV supplementation is the majority, probably due to differences between animals' and humans' epidermis, cell research cost, and the bureaucracy to conduct studies in humans. The low amount of clinical trials made it impossible for us to develop a meta-analysis. Conclusion: RSV in topical use can slow down the damage caused by sunlight's irradiation, mainly when associated with other antioxidants and in their synthesized analogous forms.